Brazing of Gr/2024Al composite and TC4 using AgCuTi filler with the assist of Ti-Al-C-Cu interlayer. (November 2019) - Shi, Junmiao; Wang, Qian; Tian, Xiaoyu; Xiong, Jiangtao; Li, Jinglong; Zhang, Lixia; Feng, Jicai
Abstract: In order to braze Gr/2024Al composite at low temperature to keep its heat insulation property, a novel thermal explosion assisting brazing method was designed. Through this method, the thermal explosion reaction of Ti-Al-C-Cu interlayer offered additional heat, and AgCuTi filler reacted with Gr/2024Al composite under the melting point of AgCuTi. Based on the theoretical calculation and DSC analysis, the composition of Ti-Al-C-Cu interlayer was designed. The microstructure and mechanical properties of brazed joint was investigated, and the brazing parameters were optimized. The results showed that AgCuTi reacted with the Gr/2024Al composite to form Ti3 AlC2 layer, and a continuous TiAl3 layer acted as the reaction layer near the TC4 alloy. The high preheating temperature and long holding time would promote the reaction of AgCuTi filler, Gr/2024Al and Ti-Al-C-Cu interlayer, and Al5 CuTi2 phase volume in the brazing zone increased. The Al5 CuTi2 distribution affected the joint strength significantly. The optimized joint strength reached 11 MPa when the joint was brazed at 650 °C for 15 min.